Alzheimer Disease: Perspectives from Epidemiology and Genetics. Issue 3 (September 2018) - Haines, Jonathan L.
Alzheimer disease (AD) is a huge and growing societal problem with upwards of 35% of the population over the age of 80 developing the disease. AD results in a loss of memory, the ability to make reasoned and sound decisions, and ultimately the inability to take care of oneself. AD has an impact not only on the sufferer, but their caretakers and loved ones, who must take on a costly and time-consuming burden of care. AD is found in virtually all racial and ethnic groups. Genetic influences on AD are substantial, and there has been a 30 year history of both success and failure. Mutations for rare early onset forms of the disease have been identified, but this information has not yet led to an effective treatment. Multiple common genetic variations have also been identified, and have led to new insights into the potential role of microglia cells in addition to neuronal cells in the brain. Despite intensive efforts, a significant portion of the genetic etiology of AD remains unknown and must be identified.